VD_FINDINFO Pron / 2012 / 1 vom 23. Dezember 2011 - VD Tribunal cantonal (2011)
DÉCISION INCIDENTE, MOYEN DE DROIT, DROIT TRANSITOIRE, DOMMAGE IRRÉPARABLE | 126 al. 1 CPC (CH), 319 let. b ch. 2 CPC (CH), 405 al. 1 CPC (CH)